PHENOTYPIC CHARACTERISATION AND GENETIC ANALYSIS OF MUTANTS OF ASPERGILLUS NIDULANS RESISTANT TO THE FUNGICIDE TOLCLOFOS-METHYL (Sciences & Technology. A, exactes sciences, 2000)
Spontaneous mutants of Aspergillus nidulans were recovered from 0,55.10+7  conidia incubated on synthetic medium supplemented with 100 mg tolclofos-methyl/ml. They differed considerably in morphology, growth rate, and level of resistance to two other fungicides. All mutants tested were cross-resistant to quintozene and vinclozolin; they produced fewer conidia than their wild-type parent. Some mutants required fungicides for maximum growth. Genetic analysis revealed that the mutants carried mutations in one gene located on linkage group III.